Gastrointestinal digestion and absorption characterization in vitro of zinc‐chelating hydrolysate from scallop adductor (Patinopecten yessoensis). (6th December 2021) - Sun, Jiatong; Liu, Xiaoyang; Wang, Zixu; Yin, Fawen; Liu, Huilin; Nakamura, Yoshimasa; Yu, Chenxu; Zhou, Dayong
Abstract: BACKGROUD: Zinc (Zn) is an essential catalytic element in the human health system but its absorption in the intestinal system can be strongly affected by gastrointestinal (GI) digestion. In this study, the food‐derived potential Zn carrier, scallop adductor hydrolysates (SAHs), was produced and characterized. RESULTS: During temporary storage at 4 °C, SAH decreased in Zn‐chelating capacity in the aqueous phase, whereas the SAH–Zn complex exhibited high stability. Moreover, the secondary structure of SAH had no significant alteration. Zn morphologically altered the surface structures of SAH, which was involving in carboxyl group of SAH. Results of in vitro GI digestion suggested that the SAH–Zn maintained good stability in GI system and only proportion of high molecular weight cleaved. In addition, SAH could successfully carry and transport Zn while the fluorescence staining revealed free Zn accumulation inside the tissue. Finally, three representative absorbed peptides (around 600 Da) were identified and synthesized. Three synthetic peptides exhibit higher Zn‐chelating capacity than SAH and could also successfully transported through the intestine. CONCLUSION: This study provided a theoretical basis for the investigation of digestion and absorption of marine animal‐derived peptides as Zn carriers. © 2021 Society of Chemical Industry.